1985
DOI: 10.1038/313703a0
|View full text |Cite
|
Sign up to set email alerts
|

Production of phenocopies by Krüppel antisense RNA injection into Drosophila embryos

Abstract: The demonstration that a specific messenger RNA can be functionally inactivated in vivo by hybridization to complementary polynucleotide sequences suggests a direct approach to the study of gene function in cells of higher organisms. The experiments described here were designed to inhibit, by complementary RNA sequences, a specific gene function affecting the fate of the Drosophila embryo. We used the SP6 vector in vitro transcription system to transcribe parts of the normally untranscribed (nonsense) strand o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(72 citation statements)
references
References 17 publications
0
72
0
Order By: Relevance
“…In the mid-1980s, several studies reported that transgenic antisense RNA could inhibit gene expression in Drosophila, mammalian cells, and plants [1][2][3][4]. This phenomenon was termed post-transcriptional gene silencing in the plant biology world.…”
Section: Introductionmentioning
confidence: 99%
“…In the mid-1980s, several studies reported that transgenic antisense RNA could inhibit gene expression in Drosophila, mammalian cells, and plants [1][2][3][4]. This phenomenon was termed post-transcriptional gene silencing in the plant biology world.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, results of a series of experiments (8,9,25,26,28,35,45) have shown that introduction of an antisense RNA complementary to a specific mRNA into cells can effectively create or mimic the null-mutant phenotype, which should be quite useful for investigating gene products of unknown physiological function. Although the exact molecular mechanism of antisense RNA inhibition of specific gene expression is not known, it has been assumed that the formation of a stable RNA-RNA hybrid in vivo results in inhibition of RNA transport, block of translation, or an increased rate of RNA turnover (25).…”
mentioning
confidence: 99%
“…Antisense RNA transcripts have been used to generate dominant mutations in eukaryotes by inhibiting the expression of specifically targeted RNA species (1)(2)(3)(4)(5)(6)(7)(8)(9), and the technique has been applied to address fundamental questions in animal molecular biology (10)(11)(12)(13)(14)(15)(16). The antisense approach in plants, if applicable, promises to make significant contributions to elucidating the functions of cloned plant genes and identifying genes with known phenotypes for which there are no biochemical markers.…”
mentioning
confidence: 99%